Predictors and Impact of Postoperative 30-Day Readmission in Glioblastoma. Issue 3 (14th September 2022) - Botros, David; Khalafallah, Adham M.; Huq, Sakibul; Dux, Hayden; Oliveira, Leonardo A. P.; Pellegrino, Richard; Jackson, Christopher; Gallia, Gary L.; Bettegowda, Chetan; Lim, Michael; Weingart, Jon; Brem, Henry; et al.
Abstract : BACKGROUND: Postoperative 30-day readmissions have been shown to negatively affect survival and other important outcomes in patients with glioblastoma (GBM). OBJECTIVE: To further investigate patient readmission risk factors of primary and recurrent patients with GBM. METHODS: The authors retrospectively reviewed records of 418 adult patients undergoing 575 craniotomies for histologically confirmed GBM at an academic medical center. Patient demographics, comorbidities, and clinical characteristics were collected and compared by patient readmission status using chi-square and Mann–Whitney U testing. Multivariable logistic regression was performed to identify risk factors that predicted 30-day readmissions. RESULTS: The cohort included 69 (12%) 30-day readmissions after 575 operations. Readmitted patients experienced significantly lower median overall survival (11.3 vs 16.4 months, P = .014), had a lower mean Karnofsky Performance Scale score (66.9 vs 74.2, P = .005), and had a longer initial length of stay (6.1 vs 5.3 days, P = .007) relative to their nonreadmitted counterparts. Readmitted patients experienced more postoperative deep vein thromboses or pulmonary embolisms (12% vs 4%, P = .006), new motor deficits (29% vs 14%, P = .002), and nonhome discharges (39% vs 22%, P = .005) relative to their nonreadmitted counterparts. Multivariable analysis demonstrated increased odds of 30-day readmission with each 10-point decrease in Karnofsky Performance Scale score (odds ratio [OR] 1.32, P = .002), each single-point increase in 5-factor modified frailty index (OR 1.51, P = .016), and initial presentation with cognitive deficits (OR 2.11, P = .013). CONCLUSION: Preoperatively available clinical characteristics strongly predicted 30-day readmissions in patients undergoing surgery for GBM. Opportunities may exist to optimize preoperative and postoperative management of at-risk patients with GBM, with downstream improvements in clinical outcomes. Abstract :